2013
DOI: 10.1007/s00125-013-2955-4
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and function of human embryonic stem cell-derived pancreatic progenitors in macroencapsulation devices following transplant into mice

Abstract: Efficient differentiation of hESC-derived pancreatic endocrine cells can occur in a macroencapsulation device, yielding glucose-responsive insulin-producing cells capable of reversing diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 54 publications
6
160
0
1
Order By: Relevance
“…transplanted per group). These devices support neovascularization via woven outer membranes, while containing the engrafted cells within cell impermeable inner membranes [18,21]. Although in our previous studies progenitor cells were transplanted under the kidney capsule [16,17], we found that macroencapsulated progenitor cells develop into human C-peptide secreting cells with similar efficiency to cells implanted under the kidney capsule (Supporting Information Fig.…”
Section: Quantitative Reverse Transcriptase Polymerase Chain Reactionmentioning
confidence: 76%
See 1 more Smart Citation
“…transplanted per group). These devices support neovascularization via woven outer membranes, while containing the engrafted cells within cell impermeable inner membranes [18,21]. Although in our previous studies progenitor cells were transplanted under the kidney capsule [16,17], we found that macroencapsulated progenitor cells develop into human C-peptide secreting cells with similar efficiency to cells implanted under the kidney capsule (Supporting Information Fig.…”
Section: Quantitative Reverse Transcriptase Polymerase Chain Reactionmentioning
confidence: 76%
“…Mature, glucoseresponsive insulin-secreting cells have only been produced from hESCs following transplantation of immature pancreatic progenitor cells; this was first demonstrated in healthy mice [12] and subsequently by our group in mice with diabetes [17,18]. We demonstrated that graft-derived human insulin levels gradually increased over time and after a 3-month maturation period, previously insulin-dependent diabetic mice achieved normal fasting blood glucose levels without exogenous insulin treatment [17].…”
Section: Introductionmentioning
confidence: 74%
“…All experiments at The University of British Columbia (UBC) with H1 cells were approved by the Canadian Stem Cell Oversight Committee and the UBC Clinical Research Ethics Board. Pluripotent H1 cells were differentiated into pancreatic progenitor cells for transplantation studies according to a 14-day, four-stage protocol, as previously described (4). Expression of key pancreatic progenitor cell markers was assessed before transplant using flow cytometry, as previously described (5); antibody information is provided in Supplementary Table 1.…”
Section: In Vitro Differentiation Of Hescs and Assessment Of Pancreatmentioning
confidence: 99%
“…Malgré ces difficultés, le champ d'application des CSE a été largement élargi par la publication en 2014 de deux études démontrant les capacités des CSE à acquérir des caractéristiques matures de cellules β in vitro. L'équipe de Kieffer, à Vancouver, a ainsi publié des révisions successives du protocole développé par ViaCyte [18,19] pour aboutir à la production, ex vivo, en 40 jours, de cellules endocrines exprimant toutes les caractéristiques de cellules β hormis le processus calciumdépendant de sécrétion d'insuline [20]. Leurs cellules β dérivées des CSE humaines étaient capables de guérir le diabète de souris dans un délai de deux mois, c'est-à-dire après une phase de maturation in vivo sensiblement restreinte.…”
Section: Progéniteurs Facultatifs Dans Le Pancréas Adulteunclassified